Effects of running-induced fatigue on joint kinematics and kinetics during overground running: a systematic review and meta-analysis - Trowell, D.; Kenneally-Dabrowski, C.; Bonacci, J. (Sports Biomechanics, 2025)
This study evaluated the acute fatigue-inducing effect of distance running on kinematics and kinetics during overground running. Standardised mean differences (SMD) with 95% confidence intervals (95% CI) were used to pool data across 16 studies. Effects during consistent (pre- and post-fatigue running speed within ± 5%) versus varied speed running (difference of >5% between running speeds) were analysed separately. There was strong evidence that running-induced fatigue significantly increases ground contact times at consistent running speeds (SMD 0.52 [95% CI 0.22, 0.82]) and moderate evidence that step length shortens at varied running speeds (SMD -1.27 [95% CI -1.79, -0.75]). There was strong evidence that fatigue does not change peak: hip and knee flexion angles, hip adduction angle, hip and knee internal rotation angles, hip and knee extension moments, hip and knee abduction moments, knee abduction angle, knee flexion and extension moments, knee adduction moment, rearfoot eversion angle, and plantarflexion moments, or knee flexion and plantarflexion range of motion during stance. Running-induced fatigue increases contact times and reduces step length, whereas lower-body joint angles and moments are unchanged. Minimising changes in stride parameters could provide a mechanism for reducing the effects of fatigue on running performance.